Pengaruh Pemberian Ekstrak Tauge Kacang Hijau (Vigna Radiata (L.)) terhadap Ketebalan Tunika Intima-Media Aorta Abdominalis pada Tikus Wistar Jantan yang diberi Stres Fisik (The Effect of Mung Bean (Vigna radiata (L.)) Sprout Extract on Tunica Intima-Me - Galuh Dharanindya Ica Manohara; Rena Normasari; Zahrah Febianti (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Mung bean (Vigna radiata (L.)) sprout contains antioxidants especially vitamin E that can prevent oxidative stress and maintain cell membranes from lipid peroxidation, so the development of atherosclerosis can be inhibited. This study investigated the effect of mung bean sprout on the aorta abdominalis tunica intima-media thickness of male wistar rats induced by physical stress. It was a true experimental study with Post-test Only Control Group Design. Twenty five male wistar rats aged 2-3 months, divided into 5 groups: K1, K2, P1, P2 and P3. K1 was a normal group without treatment. The other groups were given physical stress such as swimming test for ten days. P1, P2, and P3 group were treated by 25, 50, and 100 mg/200g/day of mung bean sprout extract simultaneously. At the end of treatment, the aorta abdominalis were taken and prepared for histopathology examination. The result showed the average of tunica intima-media thickness in K1 30,25±1,65 µm; K2 32,45±5,02 µm; P1 31,65±2,63 μm; P2 30,35±4,73 μm and P3 30,45±3,21 μm. Data analysis using One Way ANOVA showed a significancy of p=0,839. In conclusion, there was no effect of the mung bean sprout extract on tunica intima-media thickness of male wistar rats induced by physical stress. Keywords: Mung bean, physical stress, tunica intima-media